Efeito do peróxido de hidrogênio (H2O2) no íleo - Cesário, Thalyta Aparecida Munhóz [UNIFESP] (2017)
The study of reactive oxygen species becomes interesting due to production by normal cellular metabolism, in the presence of diseases and the ability to oxidize biological macromolecules. H2O2 included in the ROS class is often studied, but the effects are quite variable depending on the tissue, organ and the animal species studied. In general, H2O2 has a dual effect on biological systems, depending on concentration range, acting deleteriously at high concentrations (range of μM to mM) or as a cell marker at lower concentrations (nM range). Thus, the objective of this study was to investigate the effect of exogenous H2O2 administration in ileum isolated from mice to evaluate possible changes in morphology, redox state and antioxidant defense to further deepen the understanding of the effects of induced oxidative stress in ileum. The following results were observed: the exogenous administration of H2O2 for 20 minutes promoted changes depending on the concentration: at 100 nM concentration, was observed an increase in the thickness of the longitudinal and circular layer, with a moderate alteration of the intestinal mucosa, but an increase in lipid peroxidation. At concentrations of 100 μM and 1 mM were observed total villus destruction of the intestinal mucosa and reduction of the muscular layer. In relation to the redox state, there was a decrease in the activity of the antioxidant enzyme catalase (CAT), but of activation of the enzyme superoxide dismutase (SOD) and maintenance of levels of lipid peroxidation at concentrations of 100 μM and 1 mM. These data are indicative of the similarity of mouse ileum results as described in other animal species, that is, ileum is extremely sensitive to exogenous H2O2 administration and this compound acts positively or negatively on the structural and functional integrity of the organ.